2011
DOI: 10.1021/la104092b
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanowire Networks: Synthesis, Characterization, and Catalytic Activity

Abstract: Gold nanowire networks (AuNWNs) with average widths of 17.74 nm (AuNWN(1)) or 23.54 nm (AuNWN(2)) were synthesized by direct reduction of HAuCl(4) with sodium borohydride powder in deep eutectic solvents, such as ethaline or reline, at 40 °C. Their width and length were dependent on the type of solvent and the NaBH(4)/HAuCl(4) molar ratio (32 in ethaline and 5.2 in reline). High resolution transmission electron microscopy (HR-TEM) analysis of the gold nanowire networks showed clear lattice fringes of polycryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
94
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(98 citation statements)
references
References 33 publications
4
94
0
Order By: Relevance
“…The apparent rate constant is proportional to the surface area available for the reaction. These results help to determine the kinetics of the catalysis reaction in relation with the theoretical kinetic modeling [2,24].…”
Section: Small Angle X-ray Scattering (Saxs)mentioning
confidence: 91%
“…The apparent rate constant is proportional to the surface area available for the reaction. These results help to determine the kinetics of the catalysis reaction in relation with the theoretical kinetic modeling [2,24].…”
Section: Small Angle X-ray Scattering (Saxs)mentioning
confidence: 91%
“…The reduction of aromatic nitro groups using excess NaBH 4 in the presence of metal NPs as catalyst has been investigated. 2,[23][24][25] Very recently, shapeselective Au-Ag core-shell nanocrystals have been utilized for catalytic reduction of nitro compounds. 26 Apart from the catalysis reaction, metal NPs were also tested for surface enhanced Raman scattering (SERS) studies.…”
Section: Introductionmentioning
confidence: 99%
“…In the NWN, the special network structure imposes restrictions to the electron transport, and consequently the energy dissipation away from the excited region. In addition, Chirea et al [21] have observed an increased catalytic activity in similar Au NWN structures. They attributed this behavior on the increased number of "corners and edges".…”
Section: Resultsmentioning
confidence: 93%
“…Therefore, research regarding electron confinement in anisotropic nanostructures is increasingly pursued [1,14,15]. Recent developments in the growth of more complex, three-dimensional nanostructures [16][17][18] have shown the way for potential applications in nanodevices, nanocatalysis, nanofoams in composite materials [16,[19][20][21], and drug delivery [22]. In such nanomaterials, several open questions emerge pertinent to whether and how the ultrafast dynamical properties will depend on the peculiar shape and structure that in turn may lead to nonisotropic boundary conditions and electron confinement [1].…”
Section: Introductionmentioning
confidence: 99%